QUIET QUITTING AND LOUD POLICIES: RE-ENGAGING THE DISENGAGED WORKFORCE - Muhammad Said; Tibrani; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The post-pandemic workplace is characterized by widespread employee disengagement, manifesting as "quiet quitting”the conscious withholding of discretionary effort. Organizations often counter with generic, top-down "loud policies," which fail to address core psychological needs, deepening the engagement crisis. This study aims to analyze the disconnect between employee disengagement and organizational responses, and to propose a actionable framework for fostering genuine re-engagement. Employing a qualitative multi-method approach, the research synthesizes findings from a systematic literature review, in-depth semi-structured interviews with 35 knowledge workers across three industries, and two focused case studies of organizations undergoing cultural transformation. The analysis reveals that disengagement stems from eroded psychological contracts, burnout, and a lack of purpose. Loud policies, such as blanket RTO mandates, exacerbate these issues by signaling distrust. Effective re-engagement is predicated on psychological safety, co-created flexibility, and outcome-based management. Moving from compliance-focused mandates to human-centric leadership is essential. Sustainable engagement requires replacing loud, impersonal policies with quiet, consistent practices that rebuild trust and recognize employee agency.